Weakly supervised large-scale pancreatic cancer detection using multi-instance learning - Mandal, Shyamapada; Balraj, Keerthiveena; Kodamana, Hariprasad; Arora, Chetan; Clark, Julie M.; Kwon, David S.; Rathore, Anurag S. (Frontiers in Oncology, 2024)
Early detection of pancreatic cancer continues to be a challenge due to the difficulty in accurately identifying specific signs or symptoms that might correlate with the onset of pancreatic cancer. Unlike breast or colon or prostate cancer where screening tests are often useful in identifying cancerous development, there are no tests to diagnose pancreatic cancers. As a result, most pancreatic cancers are diagnosed at an advanced stage, where treatment options, whether systemic therapy, radiation, or surgical interventions, offer limited efficacy.Methods: A two-stage weakly supervised deep learning-based model has been proposed to identify pancreatic tumors using Computed Tomography (CT) images from Henry Ford Health (HFH) and publicly available Memorial Sloan Kettering Cancer Center (MSKCC) data sets. In the first stage, nnU-Net supervised segmentation model was used to crop an area in the location of the pancreas, which was trained on the MSKCC repository of 281 patient image sets with established pancreatic tumors. In the second stage, a multi-instance learning-based weakly-supervised classification model was applied on the cropped pancreas region to segregate pancreatic tumors from normal appearing pancreas. The model was trained, tested, and validated on images obtained from a HFH repository with 463 cases and 2882 controls.The proposed deep learning model, the two-stage architecture, offers an accuracy of 0.907±0.01, sensitivity of 0.905±0.01, specificity of 0.908±0.02, and AUC (ROC) 0.903±0.01. The two-stage framework can automatically differentiate pancreatic tumours from non-tumors pancreas with improved accuracy on HFH dataset.The proposed two-stage deep learning architecture shows significantly enhanced performance for predicting the presence of a tumor in the pancreas using CT images compared to other reported studies in the literature.